INOVASI FINANCIAL TEKNOLOGI: IDE PENGEMBANGAN KEUANGAN UNTUK MASYARAKAT PEDESAAN - Jufri, Ali (Borobudur Management Review, 2025)
Abstract Digital transformation in the financial sector has become a major catalyst for changing the paradigm of global financial services. Yet, the gap in financial access between urban and rural communities remains a significant structural barrier to inclusive economic development. This research aims to analyze the role of financial technology in enhancing access to financial services, identify the benefits of implementation for rural economic development, analyze adoption challenges, and formulate effective development strategies for rural communities. The research uses a qualitative approach with the Systematic Literature Review (SLR) method following the PRISMA protocol, analyzing 10 high-quality journals from 309 initially identified articles through the Google Scholar, SINTA, and Scopus databases for the period 2021-2025. Fintech has proven effective in reducing poverty by up to 20% in low-income provinces, with an impact twice as strong as in wealthy regions, but it faces challenges in infrastructure, digital literacy, and regulation. The implementation of comprehensive strategies, including the development of technological infrastructure, sustainable literacy programs, multi-stakeholder strategic partnerships, and adaptive regulatory frameworks, is necessary to create a sustainable and inclusive fintech ecosystem